2020
DOI: 10.3390/su12062404
|View full text |Cite
|
Sign up to set email alerts
|

Individual Factors Influencing Acceptability for Environmental Policies: A Review and Research Agenda

Abstract: To facilitate an understanding of why some environmental policies are acceptable to private citizens and why some are not, we review individual factors that influence the acceptability of environmental policy measures. The factors are categorized in demographic factors, such as age and gender, personal factors such as values and ideology, and policy specific beliefs such as perceptions of how fair or effective a policy is. The reviewed studies indicate that demographic factors generally have small effects on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 78 publications
(201 reference statements)
8
44
1
1
Order By: Relevance
“…Second, and in line with previous expectations [19,22,39], the results of the bivariate analysis showed that the acceptance of the LEZ was significantly associated with policyspecific beliefs, affect, perceived process legitimacy and trust and, to a lesser extent, with individuals' prior attitudes, such as the attitude towards the use of a car, problem perception, pro-environmental self-identity or the attitude towards pedestrianisation as well as to sociodemographics, mainly car ownership and political ideology. Clearly, all these factors deserve a place in conceptual models that try to explain the acceptability of environmental policies [22].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Second, and in line with previous expectations [19,22,39], the results of the bivariate analysis showed that the acceptance of the LEZ was significantly associated with policyspecific beliefs, affect, perceived process legitimacy and trust and, to a lesser extent, with individuals' prior attitudes, such as the attitude towards the use of a car, problem perception, pro-environmental self-identity or the attitude towards pedestrianisation as well as to sociodemographics, mainly car ownership and political ideology. Clearly, all these factors deserve a place in conceptual models that try to explain the acceptability of environmental policies [22].…”
Section: Discussionsupporting
confidence: 83%
“…Although not considered extensively in previous research, our data also showed that feelings towards the policy measure had a relevant role in acceptance. As indicated by recent reviews [22], the role of emotions such as interest, worry, anger and hope clearly requires more attention in future research. Interestingly, institutional trust had, according to our data, a very limited explanatory power.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on determinants for accepting climate mitigation policies has generated numerous studies across various academic disciplines (4)(5)(6)(7)(8). This research has applied models proposing that policyspeci c beliefs, climate change beliefs, and psychological factors determine acceptance (9,10).…”
Section: Introductionmentioning
confidence: 99%